2018
DOI: 10.1002/jbt.22046
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetyl‐cysteine mediated inhibition of spermatogonial cells apoptosis against malathion exposure in testicular tissue

Abstract: Toxicological studies so far suggest that excessive use of malathion, an organophosphate insecticide, causes serious ill-effects in mammalian reproductive physiology. The present study aims at assessing malathion-induced toxicity in a dose- and time-dependent manner with mitigating effects of N-acetyl-l-cysteine. The testicular germ cell viability was monitored using MTT assay, where NAC, being an antioxidant significantly reduced malathion-induced toxicity by enhancing the frequency of cell viability. The his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Many other in vivo and in vitro studies in animals supported the oxidative stress theory (Moridi et al 2018;Arab et al 2018); MAL-induced oxidative stress was also recently observed in many types of human cells (Durak et al 2009;Tuzcu et al 2014;Yan et al 2019;Shieh et al 2019). They found that MAL treatment leads to enhanced production of reactive oxygen species (ROS) and subsequent lipid peroxidation (Durak et al 2009;Bhardwaj et al 2018). It is evident that lipid peroxidation is accompanied by an alteration, either inhibition or activation, of the antioxidant defense system in different organs (Flehi-Slim et al 2015).…”
Section: Pharmacodynamics Of Malathionmentioning
confidence: 85%
See 4 more Smart Citations
“…Many other in vivo and in vitro studies in animals supported the oxidative stress theory (Moridi et al 2018;Arab et al 2018); MAL-induced oxidative stress was also recently observed in many types of human cells (Durak et al 2009;Tuzcu et al 2014;Yan et al 2019;Shieh et al 2019). They found that MAL treatment leads to enhanced production of reactive oxygen species (ROS) and subsequent lipid peroxidation (Durak et al 2009;Bhardwaj et al 2018). It is evident that lipid peroxidation is accompanied by an alteration, either inhibition or activation, of the antioxidant defense system in different organs (Flehi-Slim et al 2015).…”
Section: Pharmacodynamics Of Malathionmentioning
confidence: 85%
“…Histopathologically, MAL induced degenerative changes, necrosis, and edema in the interstitial tissues and seminiferous tubules (Uzun et al 2009). In vitro effects of MAL treatment, using spermatogonial cells, showed a significant reduction of testicular germ cells viability, with histopathological changes like pyknosis, vacuolization, empty spaces, tubular degeneration, and condensed or fragmented chromatin (Bhardwaj et al 2018). Biochemical tests were also affected, showing a significant decrease in testicular content of glycogen and sialic acid, in addition to a significant increase in testicular protein and cholesterol.…”
Section: Effects Of Malathion On Male Reproductive Systemmentioning
confidence: 99%
See 3 more Smart Citations